2010
DOI: 10.1111/j.1365-2036.2010.04358.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: role of acid, weakly acidic and weakly alkaline reflux in gastro‐oesophageal reflux disease

Abstract: Aliment Pharmacol Ther 2010; 32: 334–343SummaryBackground  The importance of weakly acidic and weakly alkaline reflux in gastro‐oesophageal reflux disease (GERD) is gaining recognition.Aim  To quantify the proportions of reflux episodes that are acidic (pH <4), weakly acidic (pH 4–7) and weakly alkaline (pH >7) in adult patients with GERD, and to evaluate their correlation with symptoms.Methods  Studies were identified by systematic PubMed and Embase searches. Data are presented as sample‐size weighted m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 44 publications
0
83
0
4
Order By: Relevance
“…As demonstrated by these studies, impedance-pH testing covers all possible scenarios for persistent symptoms in a treated patient: ongoing acid refl ux, ongoing non-acid refl ux, or no refl ux. Furthermore, a systematic review that quantifi ed acid and nonacid (both weakly acidic and weakly alkaline) refl ux in studies of GERD patients taking a PPI, found that weakly acidic refl ux underlies the majority of refl ux episodes in these patients and is the main cause of persistent symptoms despite PPI therapy ( 157 ). Finally, a negative impedor repeat work-up for non-GERD (pulmonary, allergic, ENT) etiologies.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…As demonstrated by these studies, impedance-pH testing covers all possible scenarios for persistent symptoms in a treated patient: ongoing acid refl ux, ongoing non-acid refl ux, or no refl ux. Furthermore, a systematic review that quantifi ed acid and nonacid (both weakly acidic and weakly alkaline) refl ux in studies of GERD patients taking a PPI, found that weakly acidic refl ux underlies the majority of refl ux episodes in these patients and is the main cause of persistent symptoms despite PPI therapy ( 157 ). Finally, a negative impedor repeat work-up for non-GERD (pulmonary, allergic, ENT) etiologies.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Media were added for 5, 10, or 30 min to equally seeded wells of subconfluent cells and then removed, and the samples were collected for analyses (see below). Exposure durations, bile acid concentrations, and pH were chosen to simulate typical episodes of gastroesophageal reflux in GERD patients who take PPIs (4,7,23,27).…”
Section: Methodsmentioning
confidence: 99%
“…w systematycznym przeglądzie piśmiennictwa podkreślili rolę refluksu słabo kwaśnego (pH = 4-7) i słabo zasadowego (pH > 7) w GERD [16]. Badacze wykazali, że w grupie pacjentów z tym schorzeniem nieprzyjmujących inhibitorów pompy protonowej (IPP) incydenty słabo kwaśne i słabo zasadowe stanowiły 37% (33-41%) ogółu epizodów GERD i odpowiadały one za 28% (13-43%) objawów klinicznych.…”
Section: Omówienieunclassified